2011
DOI: 10.1128/jcm.00504-11
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Automated Processing of Flocked Swabs with Manual Processing of Fiber Swabs for Detection of Nasal Carriage of Staphylococcus aureus

Abstract: The sensitivity of automated culture of Staphylococcus aureus from flocked swabs versus that of manual culture of fiber swabs was prospectively compared using nasal swabs from 867 patients. Automated culture from flocked swabs significantly increased the detection rate, by 13.1% for direct culture and 10.2% for enrichment culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 2 publications
4
10
0
Order By: Relevance
“…This observation is in agreement with a similar study that demonstrated a 13.1% increase in the recovery of Staphylococcus aureus by direct culture and a 10.2% increase in recovery by enrichment culture using ESwab and the WASP compared to specimens collected using traditional fiber wrapped swabs (14). Other clinical evaluations have demonstrated a 6-fold higher total CFU count and recovery of additional microorganisms from wound cultures when using ESwab compared to using traditional swabs (16).…”
supporting
confidence: 91%
See 2 more Smart Citations
“…This observation is in agreement with a similar study that demonstrated a 13.1% increase in the recovery of Staphylococcus aureus by direct culture and a 10.2% increase in recovery by enrichment culture using ESwab and the WASP compared to specimens collected using traditional fiber wrapped swabs (14). Other clinical evaluations have demonstrated a 6-fold higher total CFU count and recovery of additional microorganisms from wound cultures when using ESwab compared to using traditional swabs (16).…”
supporting
confidence: 91%
“…Advancements in technology and automation in the clinical microbiology lab have made available more efficient methods for specimen collection and processing, which have the potential to improve the sensitivity of screening and recovery of GBS and other pathogens (14)(15)(16)(17)(18). The introduction of ESwab (Copan Diagnostics, Murrieta, CA), when used in combination with the Walk-Away specimen processor (WASP) (Copan Diagnostics), has the potential to improve the efficiency and reproducibility of specimen collection, processing, and pathogen recovery through increased sensitivity, specificity, and reduced turnaround time (14)(15)(16)(17)(18)(19). Traditional fiber wrapped swabs coupled with nonnutritive transport medium, such as Liquid Stuart or Amies Gel, aid in the preservation of microorganisms during transit to the clinical laboratory; however, the inefficient transfer or release of microorganisms from a traditional fiber swab may reduce the overall sensitivity of the diagnostic procedure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the true effectiveness of automated inoculation systems needs to be validated by independent routine clinical microbiology laboratories. Compared to manual streaking, a few studies have demonstrated that the InoqulA and Previ Isola automated systems produce more isolated colonies, show better reproducibility, have no cross-contamination, and exhibit a significant decrease in hands-on plating time (2)(3)(4)(5). These studies concluded that such automated systems should improve laboratory workflow and shorten the time to results, but direct laboratory impact assessments remain to be performed to confirm these expectations.…”
mentioning
confidence: 99%
“…Lastly, they demonstrated that plating of urine transport tubes by the WASP is highly reproducible (11). Jones et al demonstrated increased detection of Staphylococcus aureus nasal colonization using ESwabs plated with the WASP in comparison to that with manually inoculated wound fiber swabs (12).…”
Section: Microbiology Specimen Processorsmentioning
confidence: 99%